1994
DOI: 10.1093/jaoac/77.6.1686
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Determination of Acid Values of Fats and Oils

Abstract: A new method for determining acid values of fats and oils was developed based on measurement of reduction prepeak current of 2-methyl-1,4-naphthoquinone (VK3) from 8 × 10−6 to 6 × 10−3 M, due to free fatty acid (e.g., linoleic acid). Acid value of 11 samples was determined. The relative standard deviation of acid value for 5 replicates of each sample was less than 2.5%. The method is superior to conventional titration methods in sensitivity and overcomes inaccuracy due to vagueness in color change of acidbase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Variations exist in the acidity determined by different alkali- metric methods endorsed by various international organizations (23). Investigations on the improvement of method sensitivity and accuracy have been based on changing the indicator (24) or by measuring the reduction prepeak current of FFA (25). The latter group also observed higher acid values with a color (phenolphthalein) indicator method than with voltammetry or potentiometry, confirming our findings.…”
Section: Resultssupporting
confidence: 86%
“…Variations exist in the acidity determined by different alkali- metric methods endorsed by various international organizations (23). Investigations on the improvement of method sensitivity and accuracy have been based on changing the indicator (24) or by measuring the reduction prepeak current of FFA (25). The latter group also observed higher acid values with a color (phenolphthalein) indicator method than with voltammetry or potentiometry, confirming our findings.…”
Section: Resultssupporting
confidence: 86%
“…29 It was reported that the reduced form of quinone (dissolved in ethanol) gave a very strong voltammetric signal in the presence of acids. For analysis of FFA in edible oils, the behavior of quinone has been utilized by various authors [30][31][32][33][34] to develop HPLC and FIA methods. The FIA system coupled with voltammetric detection gave results with a high sensitivity and better reproducibility, and the method had a low solvent consumption and an excellent throughput of 60 samples per h. Unfortunately this technique did not get much attention.…”
Section: Voltammetric Techniquesmentioning
confidence: 99%
“…e AV was calculated using the following equation [36]: acid value � titre volume × grams of NaOH in 0.1 M of NaOH solution sample weight in grams .…”
Section: Morphological Analysismentioning
confidence: 99%